MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR MATEMATIKA DENGAN MENGGUNAKAN METODE BAMBOO DANCING - Dwi Novianto (UNION: Jurnal Ilmiah Pendidikan Matematika, 2017)
The purpose of this study to describe the learning process Bamboo Dancing method to improve the activity and grade students' mathematics learning outcomes of class XI TKJ SMK N 1 Binangun, Cilacap. This type of research is the Classroom Action Research ( CAR). The subjects were students of class XI TKJ SMK Negeri 1 Binangun , Cilacap , which amounts to 40 students. Object in research is liveliness and mathematics learning outcomes. The results showed that after learning of mathematics applied to the method of Bamboo Dancing the liveliness and mathematics learning outcomes increased . Learning activeness of students has increased from the first cycle the average percentage of student activity by 48.5 % in the second cycle to 68 % . Mathematics learning outcomes of students also increased visits from the average value of 52.9 students' abilities early in the first cycle to 67.29 and the second cycle the average value becomes 82.5. KKM attainment percentage also increased from 15 % at the start capability , in the first cycle to 60 % and to 82.5 % in the second cycle. Thus Teachers are encouraged to apply the methods of Bamboo Dancing , as an alternative learning method to enhance the activity and student learning outcomes .